Abstract Mindsets Increase Believability of Spatially Distant Online Messages - Sungur, Hande; Hartmann, Tilo; van Koningsbruggen, Guido M. (Frontiers in Psychology, 2016)
Growing evidence from online credibility research reveals that online users rely on heuristic processes to evaluate the credibility of online information. The current paper, which is based on the construal level theory, proposes that congruency between the psychological distance of a stimulus and the way it is mentally construed can act as a heuristic for believability. According to construal level theory, psychologically close (e.g., spatially, temporally, socially) stimuli are represented concretely whereas psychologically distant stimuli are represented abstractly. The level of mental construals and the psychological distance of information have been shown to influence people’s truth judgments in offline contexts. This study tests whether congruency between the construal level of people’s mindsets (abstract vs. concrete) and the psychological distance implied in an online message (far vs. close) enhances message believability. By partially confirming construal level theory predictions, we found that believability of an online news item about a distant location increased when people maintained an abstract mindset rather than a concrete one. The effect of a concrete mindset on believability was not significant for the close psychological distance condition. Our findings provide initial evidence that congruency between the construal level of people’s mindsets and psychological distance cues in online messages can act as a heuristic for believability. We discuss the potential of applying the construal level theory framework to the growing literature on online cognitive heuristics in the area of online information credibility.